2011
DOI: 10.5586/asbp.2007.001
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis of selected coniferous tree species of the genera Picea, Abies and Larix

Abstract: Experiments on somatic embryogenesis in selected spruce, fir and larch species were performed to determine if this method of micropropagation enables production of quality seedlings for forest nurseries. High frequencies of embryogenic callus in spruce (23-31%) and fir (29%) were achieved when mature zygotic embryos were used as explants, while in larches (36%) only when megagametophytes (endosperms with immature embryos) were used. The possibility of somatic embryogenesis initiation also from somatic embryos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(35 reference statements)
0
1
0
1
Order By: Relevance
“…ET initiation presented itself as the major challenge in establishing a protocol. The model conifer Norway spruce (Picea abies) successfully produces ET from mature somatic embryos (Bojarczuk et al 2007), but we found that the optimal explant source was the precotyledonary immature zygotic embryo, collected from ~June 20 to ~July 10 (a develop-mental window of approximately two weeks) in eastern Ontario. Work in black pine (Pinus nigra) has demonstrated that the use of immature zygotic embryos enclosed within the intact megagametophytes is effective in producing ET that differentiate into viable somatic embryos for propagation (Salaj et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ET initiation presented itself as the major challenge in establishing a protocol. The model conifer Norway spruce (Picea abies) successfully produces ET from mature somatic embryos (Bojarczuk et al 2007), but we found that the optimal explant source was the precotyledonary immature zygotic embryo, collected from ~June 20 to ~July 10 (a develop-mental window of approximately two weeks) in eastern Ontario. Work in black pine (Pinus nigra) has demonstrated that the use of immature zygotic embryos enclosed within the intact megagametophytes is effective in producing ET that differentiate into viable somatic embryos for propagation (Salaj et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…La técnica de embriogénesis somática es un proceso de múltiples pasos que requiere el desarrollo de embriones somáticos (Méndez et al 2019). Los problemas fundamentales asociados a este método de propagación son los siguientes: la inadecuada maduración de los embriones somáticos y su limitada capacidad de germinación y conversión en plantas (Szczygieł et al, 2007;Lelu and Pâques, 2009). Solo superando estas dificultades se puede utilizar más ampliamente el método de embriogénesis somática (Hazubska et al, 2016).…”
Section: Introductionunclassified